Interventions and Cognitive Spillovers. (4th December 2021) - Altmann, Steffen; Grunewald, Andreas; Radbruch, Jonas
Abstract: This article investigates how incentives and behavioural policy interventions affect individuals' allocation of scarce cognitive resources. Based on experimental evidence, we demonstrate that incentives systematically influence individuals' allocation of cognitive resources, and their propensity to actively engage with a decision or to stay passive. Policies that steer individuals' attention to a specific decision lead to more active decision-making and better choices in the targeted choice domain, but induce negative cognitive spillovers on the quality of choices in other domains. In our setting, these two countervailing effects offset each other, such that the overall payoff consequences of the interventions are essentially zero. We further document that cognitive spillovers are especially pronounced for complex choices and for subgroups of the population with a smaller stock of cognitive resources. We discuss implications for the design and evaluation of behavioural policy interventions.